Head Impact Exposure During a Weekend Youth Soccer Tournament. (July 2016) - Chrisman, Sara P. D.; Mac Donald, Christine L.; Friedman, Seth; Andre, Jalal; Rowhani-Rahbar, Ali; Drescher, Sara; Stein, Elizabeth; Holm, Matthew; Evans, Nicole; Poliakov, Andrew V.; Ching, Randal P.; Schwien, Christina C.; et al.
Concussion is a known risk in youth soccer, but little is known about subconcussive head impacts. The authors provided a prospective cohort study measuring frequency and magnitude of subconcussive head impacts using accelerometry in a middle school–age soccer tournament, and association between head impacts and changes in (1) symptoms, (2) cognitive testing, and (3) advanced neuroimaging. A total of 17 youth completed the study (41% female, mean 12.6 years). There were 73 head impacts >15 g measured (45% headers) and only 2 had a maximum peak linear acceleration >50 g . No youth reported symptoms consistent with concussion. After correction for multiple comparisons and a sensitivity analysis excluding clear outliers, no significant associations were found between head impact exposure and neuropsychological testing or advanced neuroimaging. The authors conclude that head impacts were relatively uncommon and low in acceleration in youth playing a weekend soccer tournament. This study adds to the limited data regarding head impacts in youth soccer.